2020
DOI: 10.3390/vision4020027
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Matrix Metalloprotease MMP-9 and Tissue Inhibitor TIMP-1 in Caucasian Patients with Polypoidal Choroidal Vasculopathy

Abstract: Background: Matrix metalloproteinase 9 (MMP-9) and tissue inhibitor of metalloproteinases 1 (TIMP-1) are regulating enzymes of the extracellular matrix. A systemic imbalance of MMP-9 and TIMP-1, thought to reflect an imbalance of the extracellular matrix homeostasis, is previously associated with polypoidal choroidal vasculopathy (PCV) in Asian patients. Previous studies suggest inter-ethnical differences in the genetic background and etiology of PCV. To further explore this issue, we studied the plasma levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Levels of the biomarker TIMP-1 has previously been described as dependent on age in some studies [11,12], but to our knowledge, the possible age dependency has not been evaluated in a large cohort study.…”
Section: Introductionmentioning
confidence: 87%
“…Levels of the biomarker TIMP-1 has previously been described as dependent on age in some studies [11,12], but to our knowledge, the possible age dependency has not been evaluated in a large cohort study.…”
Section: Introductionmentioning
confidence: 87%
“…MMP9, which is involved in extracellular matrix metabolism, was found to be associated with Asian patients with PCV. Another study reported that MMP9 was not found in White patients with PCV 37…”
Section: Updates On Risk Factors and Biomarkers For Pcv Developmentmentioning
confidence: 97%
“…[4][5][6] Some increased cytokine levels in plasma with a link of PCV or nAMD exclusively, suggesting that the 2 disorders may have different molecular mechanisms. 7,8 However, most existing studies on plasma markers of inflammation and angiogenesis in AMD rarely distinguish nAMD from PCV, even some kinds of cytokines in PCV or nAMD do not have altered levels of plasma compared to healthy controls; [9][10][11] while a recent study reported differences between plasma proinflammatory cytokines possessed a positive but weak ability in discriminating nAMD from PCV, indicating that PCV differed from nAMD in terms of plasma inflammation profile. 8 Therefore, the aim of this study was to further investigate markers of inflammation and angiogenesis in plasma of patients with PCV and nAMD and to identify differences in cytokine profiles between these diseases comprehensively.…”
Section: Introductionmentioning
confidence: 99%